Optimalisasi Pembiayaan Syariah pada Koperasi Al-Ikhlas: Tinjauan Hukum Islam - Taufik Hidayat Harahap (Cv. Kalimasada Group, 2023)
This study aims to analyze the implementation of Islamic principles in financing practices at the Al-Ikhlas Cooperative of the Ministry of Religious Affairs (Kemenag) Pidie and assess the compliance of the provided financing with Islamic law. The study also aims to identify the strengths and weaknesses of the financing system implemented and provide recommendations for improving the application of Islamic principles at the cooperative. Using a qualitative approach and a case study method, data were collected through interviews with the cooperative’s management and members, as well as direct observation of the financing process. Data analysis was conducted descriptively to illustrate the financing practices and relate them to Islamic principles. The results of the study show that most of the financing practices applied by the Al-Ikhlas Cooperative are in line with Islamic law. Akads such as murabaha and musharakah are used to ensure fairness, transparency, and avoid elements of riba, gharar, and oppression. However, there are weaknesses related to the unclear setting of profit margins and the underutilization of the profit-sharing system. Therefore, it is recommended that the cooperative clarify the profit margins and optimize the use of the profit-sharing system to further enhance compliance with Islamic principles.